2016
DOI: 10.1016/j.phrs.2016.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal cancer: The latest on chemoprevention and state of the art therapies

Abstract: Esophageal cancer is currently the 8th most common cancer worldwide and the 6th leading cause of cancer-related mortality. Despite remarkable advances, the mortality for those suffering from esophageal cancer remains high, with 5-year survival rates of less than 20%. In part, because most patients present with late-stage disease, long-term survival even after resection and therapy is disappointingly low. As we will discuss in this review, multiple characteristics specific to the disease stage and patient must … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 94 publications
0
30
0
Order By: Relevance
“…Radical surgery is the standard treatment that can provide opportunities for a cure. However, the 5‐year survival rates for surgically resectable ESCC are still unsatisfactory and range from 15% to 30% . Although adjuvant chemotherapy and radiotherapy have been shown to improve disease‐free survival rate .…”
Section: Discussionmentioning
confidence: 99%
“…Radical surgery is the standard treatment that can provide opportunities for a cure. However, the 5‐year survival rates for surgically resectable ESCC are still unsatisfactory and range from 15% to 30% . Although adjuvant chemotherapy and radiotherapy have been shown to improve disease‐free survival rate .…”
Section: Discussionmentioning
confidence: 99%
“…Due to advances in surgical techniques and multi-modality treatments, the prognosis of non-metastatic esophageal cancer has slowly improved over the past decades (3,4). However, the overall 5-year survival probability is still poor and needs to be considerably improved (5). This is particularly true for patients with locally advanced unresectable disease.…”
mentioning
confidence: 99%
“…According to the 2018 global cancer epidemiology report, esophageal cancer (ESCA) currently has the 7th highest incidence and is the 6th leading cause of mortality., while the ESCA mortality in developing countries tends to rise [1]. Although the e ciency of advanced diagnosis and multidisciplinary therapy for ESCA have demonstrated a notable improvement recently, data from the last decade showed that the 5-year overall survival (OS) rates in the US, China, and Europe are 22.0%, 20.9%, and 12.6%, respectively, and 70% of patients have missed the opportunity of undergoing radical surgery on rst diagnosis because of their late disease stage [2][3][4][5]. Related studies have shown that immunotherapy signi cantly prolong the survival of advanced gastric or gastro-oesophageal junction cancer patients (8.2 months: 7.1 months, hazard ratio (HR) = 0.78, 95% con dence interval (CI): 0.63-0.96, P = 0.0095), but in all patients with ESCA, the effective rate is only 13.1% (41/314) [6].…”
Section: Introductionmentioning
confidence: 99%